Video-assisted thoracoscopic surgery vs. open thoracotomy in the management of empyema: A Meta-analytical perspective - Sudarma, I Wayan; Yasa, Ketut Putu; Harta, I Komang Adhi Parama; Pertiwi, Putu Febry Krisna (Indonesian Vascular Access Association (IVAA), 2024)
Background: Pleural empyema is a serious condition requiring surgical intervention in advanced stages. This systematic review and meta-analysis compared the outcomes of video-assisted thoracoscopic surgery (VATS) and open thoracotomy in the management of pleural empyema. Method: After performing a systematic search on electronic databases, 15 studies were included with a total of 1,795 patients. Result: The results demonstrated that VATS was associated with significantly shorter chest tube duration (MD: −2.68 days, 95% CI: −4.22 to −1.13, p < 0.001), reduced rates of prolonged air leak (OR: 0.44, 95% CI: 0.26 to 0.74, p = 0.001), and lower total complications (OR: 0.62, 95% CI: 0.44 to 0.87, p = 0.006). Mortality, reoperation rates, and recurrence rates were comparable between VATS and open thoracotomy, indicating similar efficacy for long-term disease resolution. In conclusion, this analysis highlights the advantages of VATS as a minimally invasive approach, particularly in reducing postoperative morbidity and complications. Conclusion: Open thoracotomy remains crucial for complex or advanced cases requiring extensive decortication. The findings underscore the importance of individualized surgical decision-making based on disease stage and patient characteristics.